Effect of reciprocal crossing Koekoek and Sasso chickens on growth performance, feed efficiency, carcass yield, mortality rate, and genetic components - Itafa, B.T.; Mohamed, A.S.; Abate, W.H.; Derseh, M.A.; Woldegiorgiss, W.E. (Elsevier, 2021)
Reciprocal crosses of Koekoek and Sasso chickens were evaluated for growth performance, feed efficiency, carcass yield, mortality rate, and genetic components using 60 randomly selected 8-wk-cockerels (15 from each mating group) at Jimma University poultry farm. Data were measured for initial and final body weight, feed intake, daily weight gain, and feed conversion ratio. At the end of the study, following a 4-h fasting period, chickens were weighed, humanely slaughtered, and dressed. Carcass weight, dressing percentage and amount and percentage of abdominal fat were determined. Mortality was recorded. Genetic components were calculated. The collected data were analyzed using the General Linear Models (GLM) procedure of the Statistical Analysis System other than mortality rate and genetic components. Mortality rate and genetic components were analyzed using GLIMMIX Procedure of SAS version 9.4. The study revealed that the cross of Koekoek (cockerel) × Sasso (pullet) (KS) performed significantly (P < 0.05) better than the cross of Sasso (cockerel) × Koekoek (pullet) (SK) for final body weight (2615 g vs. 2208 g), feed intake (133 g vs. 93.3 g), daily weight gain (23.7 g vs.18.3 g), empty carcass weight (2006 g vs. 1604 g), and dressing percentage (77.1 g vs. 72.6 g). Further, the KS group survived significantly (P < 0.05) better than SK with the lowest mortality rate during the experimental period (0.004 vs. 0.009). KS has performed positively and highly in heterosis percentage (H %) for all parameters while SK has performed negatively for former traits. Thus, the crossing of Koekoek cockerels with Sasso pullets should be preferred to its reciprocal cross to obtain higher levels of heterosis for growth performance, feed efficiency, and carcass yield.